Implementasi Alat Pemantau Debit dan Ketinggian Air Sungai Berbasis Internet of Things Untuk Penanggulangan Banjir - Cep Lukman Rohmat; Odi Nurdiawan; Irfan Ali; Arif Rinaldi Dikananda; Athhar Hafizha Luthfi; Eti Rohayati (Journal of Computer System and Informatics (JoSYC), 2023)
The increasing frequency and intensity of floods in Cirebon City demands innovative solutions to reduce the impact of damage and risks to society and infrastructure. requires the latest approaches to risk management and prevention. This research focuses on the implementation of an Internet of Things (IoT)-based river discharge and water level monitoring tool designed to improve flood detection and prevention capabilities in Cirebon City. The main problems faced include accurate measurements, real-time monitoring, and rapid response to river water fluctuations. By combining the latest sensors and IoT technology, this tool is able to provide accurate data about water discharge and river levels continuously. The first stage in developing the Internet of Things (IoT) is identification and study of flooding problems in Cirebon City and analysis of the need for a monitoring system for flood prevention. Second, design a monitoring tool concept that meets the needs and specifications and determine the type of sensors, hardware and IoT technology that will be used. Third, choose a sensor to measure river discharge and water level. Fourth, build a monitoring tool prototype based on conceptual design. Fifth, Testing and Validation. The results of this research are based on river tests in the city of Cirebon, there are 4 rivers that frequently flood and the results of the test are that the Kalijaga River has a height of 20cm in the Safe level category, the Kedung Pane River has a height of 15cm in the Safe Level Category, the Kesunean River has a height of 10cm in the Safe Level Category and the Sukalila River has a height of 17cm in the Safe level category this is influenced by dry weather. Then the data collected from monitoring tools can be used to analyze flood patterns, trigger factors and impacts. Then, from this data, a flood classification analysis can be carried out based on the level of river water discharge, so that it can be classified as light, medium or heavy floods based on the amount of water flowing.